1996
DOI: 10.1212/wnl.47.1.208
|View full text |Cite
|
Sign up to set email alerts
|

Speech timing in ataxic disorders

Abstract: We studied syllabic timing in patients with ataxia (10 with cerebellar atrophy, 6 with Friedreich's ataxia) under two conditions: in a "natural" sentence production context and in the context of a rapid syllable repetition task. The two tasks included comparable articulatory maneuvers. We measured syllable durations from the speech signal and analyzed variables describing average syllabic rate and within-trial variation of syllable durations. Among the observed measures, slowed syllable repetition was a partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 14 publications
7
52
1
1
Order By: Relevance
“…The slowed articulatory rates for speakers with MS were further evidenced by lengthened syllable and gap durations. These findings are in agreement with previous studies reporting slowed DDK rates for individuals with ataxic and spastic dysarthria [e.g., 6,9,12,13,15,16]. In contrast to previous research [12], however, qualitative inspection of the data indicated that speakers with ataxic dysarthria did not disproportionately lengthen gap durations nor did speakers with spastic dysarthria disproportionately lengthen syllable durations.…”
Section: Global and Segmental Timing Measuressupporting
confidence: 90%
See 1 more Smart Citation
“…The slowed articulatory rates for speakers with MS were further evidenced by lengthened syllable and gap durations. These findings are in agreement with previous studies reporting slowed DDK rates for individuals with ataxic and spastic dysarthria [e.g., 6,9,12,13,15,16]. In contrast to previous research [12], however, qualitative inspection of the data indicated that speakers with ataxic dysarthria did not disproportionately lengthen gap durations nor did speakers with spastic dysarthria disproportionately lengthen syllable durations.…”
Section: Global and Segmental Timing Measuressupporting
confidence: 90%
“…Increased temporal variability or irregularity of DDK is thought to be most characteristic of ataxic dysarthria [13][14][15]. However, increased temporal variability also has been reported for speakers with spastic and hypokinetic dysarthria, relative to healthy controls [6,9,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…. In the literature there are reports on speed reduction, worsen of accuracy and inconsistency of oral diadochokinesia in a large range of neurological disorders and even in some functional disorders 3,8,[10][11][12][13][14][15][16] . Generally, the ataxias seem to produce a greater impact on the diadochokinesia with an important reduction of the speech rate 16 , despite of some differences pointed out in Parkinson' s disease 15 .…”
Section: Dra Marina Padovani -Rua Brás Cardoso 223 -04510-030 São Pamentioning
confidence: 99%
“…Generally, the ataxias seem to produce a greater impact on the diadochokinesia with an important reduction of the speech rate 16 , despite of some differences pointed out in Parkinson' s disease 15 . The diadochokinesia test has been correlated with clear articulation 3 , dysartria severity and speech inteligibility 13 . Although it is a relatively simple test, there…”
Section: Dra Marina Padovani -Rua Brás Cardoso 223 -04510-030 São Pamentioning
confidence: 99%
“…One limitation to this study, however, is the use of subjective ratings based on an unvalidated measure of dysarthria. In the present study we endeavored to improve upon prior research by widening the scope of cognitive testing and using an objective measure of oral motor speed known as the Maximum Repetition Rate of Syllables and Multisyllabic Combinations task (MRR; Kent et al, 1987), which has well-established reliability (Kreul, 1972) and validity (Dworkin et al, 1980;Portnoy & Aronson, 1982;Tatsumi et al, 1979;Ziegler & Wessel, 1996).…”
Section: Introductionmentioning
confidence: 99%